Аналіз стану інноваційної діяльності в Україні та шляхи його поліпшення - Яковлєв, Анатолій Іванович (Інститут досліджень науково-технічного потенціалу та історії науки імені Г. М. Доброва НАН України, 2018)
Розглянуто показники рівня інноваційного розвитку в Україні. Проаналізовано три його складові — економічну, соціальну, законодавчу. Висвітлено проблеми в сфері інноваційної діяльності в Україні: недостатнє фінансування, застаріла матеріально-технічна база. Підкреслено необхідність поліпшення підготовки кадрів і стимулювання їх роботи. Запропоновано методи вибору пріоритетів інноваційного розвитку, розрахунку ефективності кредитування інновацій, стимулювання створення і реалізації інновацій. Зокрема, розроблено та апробовано модель визначення величини відсотка за кредит за результатами конкретного інноваційного проекту. Розглянуто шляхи розвитку державної підтримки інноваційної діяльності.

Innovating and innovations are a primary factor for the development of a national economy. As the innovation performance in Ukraine remains to be low, system studies focused on identifying its reasons and finding the ways for the performance enhancement are of great practical importance. The article’s objective is to scrutinize the innovation performance in Ukraine and offer ways to improve it. Indicators measuring the innovation performance in Ukraine are shown. Its three components, economic, social and legal, are analyzed. The economic component can be improved by setting up priorities of the innovation-driven development with consideration to the financial and time limits, the extended participation of domestic businesses in value added chains of transnational corporations, elaborating an advanced domestic method for assessing the effectiveness of innovations. The social component can be enhanced through creating new jobs and elaborating an advanced system for stimulations to innovators. The legal component can be improved though adjusting the taxation system to the innovation-specific purposes, to the needs of domestic producers protection, stimulation of domestic investment in the Ukrainian economy, government guarantees to investors etc. Perpetual problems faced by the innovation sector in Ukraine (poor financing, out-dated technical facilities) are highlighted. Methods for innova tion priority setting, for evaluation of the effectiveness of innovation lending, for stimulation of innovating are proposed. A model for assessing interest rates on loans by the results of specific innovation projects is constructed as part of the study, and tested by data from 20 outstanding innovation-investment projects in Ukraine. A review of successful stories of innovation stimuli in Ukraine and beyond is given. Measures of government support to innovating are discussed.
Analysis of the innovation performance in Ukraine and ways for its enhancement
Keywords: інновації; рівень розвитку; фінансування; кредитування; підготовка кадрів; стимулювання; innovation; level of development; financing; lending; staff training; state support